Priority Banking Services in Indonesia in Islamic Perspectives - Yaser Taufik Syamlan; Abdurrahman Misno Bambang Prawiro (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
The purpose of the study is to analyze the practice of Priority Banking in Indonesia at PT. Bank Syariah Mandiri (hereinafter referred to as BSM), especially in the use of wadiah contracts in priority banking services. The research method is normative legal studies with analysis using Usul Fiqh to identify the presence or absence of usury in priority banking services. Data is obtained through observation techniques, direct interviews and document studies. The results of this study are that there are 3 types of Priority Banking Services offered to customers both from deposits with wadiah or mudharabah contracts, namely Financial Services, Non-Financial Services, and Special Programs for Priority Banking Customers. The three services are funded by BSM internal cash. Priority banking services conducted by BSM violated the provisions of the DSN-MUI fatwa No. 01/DSN-MUI/IV/2000 regarding Current Account and DSN-MUI fatwa No. 02/DSN-MUI/IV/2000 which states that the banks are not permitted to give bonuses if promised in advance. This study concludes that for services which yield material benefits that have a wadiah contract, then it is usury. However, if it yields immaterial benefits, it is not usury so that it is permitted.